Gastrointestinal nematodes and mineral deficiencies in yearling cattle in Santiago del Estero, northern Argentina - Suarez, Victor Humberto; Martinez, Gabriela Marcela; Olmos, Leandro Hipolito; Rossanigo, Carlos Esteban (Springer, 2022)
The aims were to study the epidemiology and the effect of gastrointestinal nematodes (GINs) on yearling cattle in a semiarid region in Argentina and to evaluate the mineral serum levels. Ten- to twelve-month-old calves were monitored between November and April 2019. Animals were divided into three groups: untreated control (CONG; n = 20); group treated with moxidectin (MXD, 200 µg/kg) every 30–40 days (MXDG; n = 20); group equally MXD treated and mineral supplementation administered in November and January (MMG; n = 20). Individual GIN egg counts (epg) and fecal cultures were made every 30–40 days. Animal live weight gain was determined. On 7–11-18, 25–1-19, and 3–4-19, serum levels of Se, Cu, Zn, Mg, and Ca were determined by atom absorption spectrophotometry. At the start of the trial, epg values were low (x̄ = 5.5), which increased only in CONG towards the end of the assay (x̄ = 229). In both GMXD and MMG, epg remained very low (x̄ = 4.1). Cooperia spp. (81%) prevailed over Haemonchus spp. (9%) and Oesophagostomum spp. (9%). Deficiency of Se ranged between marginal and important, except for MMG, although mean values were always below normal. Cu was marginally deficient in CONG and MXDG on the first two sampling dates, whereas MMG had normal values after treatment. Mg had low values in the three groups (x̄ = 1.5 mg/dl), whereas Ca and Zn exhibited normal values. Live weight gain (LWG) was higher in MMG than in MXDG, with significant differences (p < 0.05) by mid-January and then, when epg increased, dewormed groups showed higher LWG (p < 0.034) than CONG. A negative effect of GINs on LWG was observed, as well as low to marginal levels of Se, Cu, and Mg.